2012
DOI: 10.1134/s1070427212010284
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a polytetrafluoroethylene coating deposited onto polyester fibers from supercritical carbon dioxide

Abstract: A low-molecular-weight polytetrafl uoroethylene coating deposited onto a polyester textile material from supercritical carbon dioxide with the aim to make the material hydrophobic was analyzed. The hydrophobic properties of the coating were examined in comparison with those of the hydrophobizing agent produced by Nuva (Switzerland).The most effective surface modifi ers used for making the surface unwettable are fl uorinated hydrocarbons having low surface energy (18.5-26 mJ m -2 ) [1]. In hydrophobization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In this concern, solving the above discussed difficulties of PTFE in the textile processing is a common expectation of in textile industry. The developed methods (emulsion dipping, laminating composite method, and sputter coating) [8,9] are mainly based on coating of PTFE materials on the fabric, which will invalidate the fabric washability, [10] air permeability, [11] comfort, [12] style. [13] Moreover, the high molecular weight of PTFE makes it difficult to adhere to the fabric surface and the coating on fiber surface is uneven because of Plateau-Rayleigh instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this concern, solving the above discussed difficulties of PTFE in the textile processing is a common expectation of in textile industry. The developed methods (emulsion dipping, laminating composite method, and sputter coating) [8,9] are mainly based on coating of PTFE materials on the fabric, which will invalidate the fabric washability, [10] air permeability, [11] comfort, [12] style. [13] Moreover, the high molecular weight of PTFE makes it difficult to adhere to the fabric surface and the coating on fiber surface is uneven because of Plateau-Rayleigh instability.…”
Section: Introductionmentioning
confidence: 99%
“…Why in most cases PTFE materials are only used in industrial textiles and seldom used in apparel textiles? The reason is that the small dielectric constant value of PTFE makes it easy to generate static electricity during friction, [ 8 ] which will result in the failure of normal production of PTFE fabric, let alone high‐speed production. Specifically, the static electricity will cause unclear shedding (warp yarn weaving opening), mechanical failures or even major accidents.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of the processed fabric (a) 2, (b) 2 and 3 have similar bands, unlike the spectra of the initial fabric (a) 1, (b) 1, which indicates the formation of a fluorine-containing coating on the fabric surface. The formation of a coating with PTFE properties on the polyester fabric surface is also confirmed by the X-ray diffraction, energy-dispersive, gravimetric, elemental and thermal analyses [18,43,44,49,50].…”
Section: Resultsmentioning
confidence: 64%
“…When applied from solutions, some of these oligomers are capable of forming coatings on the surface of filaments with properties similar to those of polytetrafluoroethylene [220,221]. Fluorinated oligomers, obtained either by thermal degradation of fluoropolymers [207,[222][223][224][225][226][227] or by synthesis from fluoromonomers [3,207,211,221,[228][229][230][231][232], are the basis of such coatings. The use of organosilicon compounds as hydrophobizers also significantly reduces the surface energy of fibrous materials [233][234][235][236].…”
Section: Hydrophobic Propertiesmentioning
confidence: 99%
“…Fabrics and nonwovens are formed by cylindrical fibers and threads, which are characterized by a higher water contact angle than flat films of the same chemical composition [260]. In addition, in previous works [223,224,261,262] it was shown that fabric has a multimodal roughness, due to its complex weave. These factors create favorable conditions for the hydrophobization of fibrous materials and contribute to the achievement of higher water contact angle compared to the treatment of films of similar chemical composition with the same hydrophobizer.…”
Section: Hydrophobic Propertiesmentioning
confidence: 99%